THE EFFECT OF WORK-LIFE BALANCE ON EMPLOYEE WORK MOTIVATION WITH BURNOUT AS A MEDIATING: A SURVEY ON EMPLOYEES OF PT. CHAROEN POKPHAND JAYA FARM - Sheni Pratiwi Hermawati Sheni Pratiwi Hermawati; Sheni Pratiwi Hermawati (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
This study explores how work-life balance (WLB) affects employee work motivation, with burnout considered as a mediating variable. The research was conducted at PT. Charoen Pokphand Jaya Farm, a company in the agribusiness sector. The background of this study lies in the observation that some employees experience difficulties in maintaining motivation due to stress from workload and imbalance between work and personal life. Using a quantitative approach, data were collected through questionnaires distributed to 133 employees and analyzed using the Statistical Package for the Social Sciences (SPSS) version 26. The results show that work-life balance has a significant positive effect on motivation, while burnout has a significant positive effect on motivation. Additionally, burnout partially mediates the relationship between work-life balance and motivation. This means that a good balance between personal life and work can reduce burnout, which in turn helps maintain or increase employee motivation. The findings contribute to understanding how HR management can create healthier work environments in the agribusiness sector, especially through supportive policies that promote work-life balance.